Kualitas Daun Binahong (Anredera cordifolia) pada Suhu Pengeringan Berbeda - Hesti Fajar Utami; Rini Budi Hastuti; Endah Dwi Hastuti (Jurnal Akademika Biologi, 2015)
Binahong leaf is one of the plants that can be used as a traditional medicine. An important step in the use of leaf binahong as drugs is by drying. This study aims to determine the effect of different drying temperature treatment on quality of leaf binahong. The research is divided into two stages: 1. to investigate binahong leaf quality of weight loss changes, the color and texture  of the leaves binahong after different drying; 2. to investigate flavonoid quality changes after different drying. The study design used was completely randomized design (CRD) with one factor, namely the factor of temperature drying 270C,300C  temperature,  the  temperature  of  400C  and  500C  temperature  for  1  day.  The parameters of this study consisted of weight loss percentage, percentage of water content, leaf  color,  leaf  texture  and  flavonoid  content  analysis.  Analysis  of  the  data  used  isAnalysis  of  Variance  (ANOVA)  followed  by  Duncan's  real  different  test  at  95%significance level. The results showed that the drying temperature tends to increase the rate of weight loss, eliminating moisture, affect change in color and texture of the leaves and reduce the content of flavonoids. Drying temperature 500C showed the best results in reducing weight loss  and moisture content, but is not able to maintain the color and texture of the leaves and leaf flavonoid content binahong, while the temperature of 270C, a temperature of 300C and 400C temperature is able to maintain the color and texture of the leaves but slightly lowers weight  loss  and levels water. The highest binahong leaf flavonoid  produced  at  a  temperature  of  270C  is  equal  to  10,729%  followed  by  a temperature of 300C at 1,305%, 0,753%  temperature of 400C and 500C temperature of0,651, so  it  is  recommended  to  use  as  a traditional  medicine,  the  leaves  should be consumed directly binahong. Keywords: Anredera cordifolia, drying temperature, flavonoid